Gelidium sanyaense sp. nov. and G. yangmeikengense sp. nov. (Gelidiales, Rhodophyta) from southern China based on morphology and molecular data. Issue 1 (1st January 2018) - Wang, Xulei; Xia, Bangmei; Boo, Ga Hun; Wang, Guangce
Abstract: Taxonomic confusion has been a significant problem with the small species of Gelidium because of their simple and variable morphology. In this study, specimens of two turf-forming species from southern China were studied on the basis of morphology and molecular data. Both data sets revealed the presence of two novel species in Gelidium : G. sanyaense sp. nov . and G. yangmeikengense sp. nov ., described here. Gelidium sanyaense, forming sparse or dense turfs along the coast of southern China, was distinguished by the presence of compact brushlike haptera, a flattened and lanceolate axis, simple branches, and sparse medullary cells surrounded by rhizines. Gelidium yangmeikengense was characterized by a broad, stipelike axis that was constricted at the base, broadened in the middle and attenuated upward to become slender and cylindrical, and by sparsely pinnate branches on the upper portion of the axis. In phylogenies of both COI and rbc L sequences, G. sanyaense and G. yangmeikengense were distantly related and formed separate monophyletic clades.